External supervesical hernia. A case report - Y. M. Kovgan (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
The paper presents a case report of diagnosis and treatment of external supravesicalis hernia after operation on the inguinal hernia in the volume of laparoscopic transabdominal preperitoneal plastic. A man, 49 years old, re-enrolled by recommendation from the polyclinic with a diagnosis "recurrence of the inguinal hernia on the right". Ten months before the patient had undergone laparoscopic transabdominal preperitoneal plastic surgery on the right inguinal hernia. Due to the high BMI (34.5 kg/m2) and objective doubts about the relapse, computed tomography of the abdominal cavity with intravenous contrasting was performed, which revealed a hernial protrusion in the suprapubic region. There was no intraoperative defect detected in the area of previously performed hernioplasty, but the test confirmed peritoneal protrusion medially to the lateral umbilical fold. After mobilization of the peritoneum of this region, a hernial defect was found about 2.5 cm in diameter, formed by the medially pyramidal muscle, from below the pubic bone and laterally by the rectus abdominal muscle. The contents of the hernia was urine fat. A mesh (5 x 7 cm) denture was installed with stapler fixation. The patient was discharged on the third day after the surgery. The follow-up period was about 12 months. Data for recurrence of hernia or dysuric phenomena were not found.